Teachers' belief as correlates of coping with problems affecting english learning among secondary school students in Ibadan (2023)
This study examined teachers’ belief (Beliefs about learners and learning, Beliefs about teaching, Beliefs about the curriculum) as correlates of coping with problems affecting English learning among students in Ibadan. The survey research design of the correlational type was adopted. Fifteen (15) secondary schools were purposively selected from five local government areas in Ibadan. Two English language teachers were selected from each school, making a total of 30 English language teachers as the sample size. Teacher’s Belief Questionnaire (r=0.91) and Coping With Factors Affecting English Questionnaire (r=0.89) were used for data collection. The Pearson Product Moment Correlation and Multiple Regression Analysis were used for data analysis and the results were interpreted at 0.05 level of significance. Findings revealed that coping with factors affecting English language learning among students had positive significant relationship with Teachers’ beliefs about Learners and Learning (r = 0.96); beliefs about teaching (r = 0.83); belief about curriculum (r = 0.81). There was a significant joint contribution of teachers’ beliefs (F (3; 26) = 264.66; p = 0.00 < 0.05), while teachers’ belief about Learners and Learning (β = 0.97, t = 0.99; p = 0.03 < 0.05), had significant and highest relative contribution, followed by Teachers’ Belief about teaching (β = - 1.14, t = - 6.13; p = 0.00 < 0.05). English language teachers therefore need to be dynamic in their instructional delivery rather than holding unto beliefs that may not be helpful in coping with factors affecting English language learning among students.